Systemic Bartonella henselae Infection in Immunocompetent Adult Presenting as Fever of Unknown Origin - Thierry Zenone (Case Reports in Medicine)
Systemic clinical presentations of infection caused by Bartonella henselae are rare in immunocompetent adults. We report four cases with hepatic and/or splenic involvement, presenting as fever of unknown origin. We discuss diagnosis and treatment of this infection. Bartonella henselae serology allows an easy diagnosis of hepatosplenic involvement in cat scratch disease, a clinical picture that appears to be underrecognized.